Population‐specific dynamics and selection patterns of transposable element insertions in European natural populations. Issue 6 (17th January 2019) - Lerat, Emmanuelle; Goubert, Clément; Guirao‐Rico, Sara; Merenciano, Miriam; Dufour, Anne‐Béatrice; Vieira, Cristina; González, Josefa
Abstract: Transposable elements (TEs) are ubiquitous sequences in genomes of virtually all species. While TEs have been investigated for several decades, only recently we have the opportunity to study their genome‐wide population dynamics. Most of the studies so far have been restricted either to the analysis of the insertions annotated in the reference genome or to the analysis of a limited number of populations. Taking advantage of the European Drosophila population genomics consortium ( DrosEU ) sequencing data set, we have identified and measured the dynamics of TEs in a large sample of European Drosophila melanogaster natural populations. We showed that the mobilome landscape is population‐specific and highly diverse depending on the TE family. In contrast with previous studies based on SNP variants, no geographical structure was observed for TE abundance or TE divergence in European populations. We further identified de novo individual insertions using two available programs and, as expected, most of the insertions were present at low frequencies. Nevertheless, we identified a subset of TEs present at high frequencies and located in genomic regions with a high recombination rate. These TEs are candidates for being the target of positive selection, although neutral processes should be discarded before reaching any conclusion on the type of selection acting on them. Finally, parallel patterns of association between the frequency of TE insertions and several geographical and temporal variables were found between European and North American populations, suggesting that TEs can be potentially implicated in the adaptation of populations across continents.